COVID-19 PANDEMIC-KNOWLEDGE, PERCEPTION, ANXIETY AND DEPRESSION AMONG FRONTLINE HEALTHCARE WORKERS OF AYUB TEACHING HOSPITAL ABBOTTABAD, PAKISTAN - Saqib Malik,; Rehman, Najma; Farhat Naz,; Sadia Rehman,; Zainab Syed,; Huma Mushtaq,; Abdul Haseeb, (Journal of Ayub Medical College Abbottabad, 2022)
Background: The COVID-19 pandemic is a viral infection that spreads through different mediums and has a high rate of mortality. At its initial stages, there is no particular medicine that can cure patients of COVID -19. The aim of the present study was to understand the COVID-19 knowledge, perception, and its effects in terms of anxiety and depression among frontline health care workers of Ayub Teaching Hospital, Abbottabad. Methods: This cross-sectional study was conducted in Ayub Teaching Hospital, Abbottabad from June 2021 to Jul 2021 in which data was collected from 200 hospital healthcare workers who have performed duties in COVID isolation wards through standard questionnaire. SPSS version 24.0 was used for data analysis. Results: Out of 200 participants in the study 100 (50.0%) were male. Regarding safety measures taken during COVID -19, 144(72.0%) individuals reported that they have not been given training to handle known or suspected cases of COVID -19. Moderate anxiety and depression was found in 153 (76.5%) healthcare workers, mild in 25 (12.5%) and 22(11.0%) had severe anxiety and depression at the time of COVID -19 pandemic. Conclusion: This study revealed that a significant anxiety and depression was found in frontline healthcare workers during the COVID-19 pandemic. In addition, a more extensive study should be conducted which involves many other hospitals like Ayub Teaching Hospital.